(untitled) (Anclajes, 2024)
This essay locates the theoretical scene of transatlantic criticism within the dialogical context of literary studies, whose European origins and Latin American elaborations account for variants and articulations that meet to create a horizontal tradition of critical knowledge. The author argues that transatlantic criticism also corresponds to the concept of the complementary of the cultural traditions both of originary languages and literatures, making language (Inca Garcilaso de la Vega, Guamán Poma de Ayala, José María Arguedas) a place not of binary oppositions but of inclusive and sequential collectivities and constructions. A hypothesis of literature as hospitality is consequently proposed as the task of criticism.